THE PROBLEM OF ANONYMITY AND PSEUDONYMITY IN CHRISTIAN LITERATURE OF THE FIRST TWO CENTURIES1 - Aland, Kurt (The journal of theological studies, 1961)
K. ALAND; THE PROBLEM OF ANONYMITY AND PSEUDONYMITY IN CHRISTIAN LITERATURE OF THE FIRST TWO CENTURIES1, The Journal of Theological Studies, Volume XII, Issue 1